Emergent Fermi Surface in a Triangular-Lattice SU(4) Quantum Antiferromagnet - Keselman, Anna; Bauer, Bela; Xu, Cenke; Jian, Chao-Ming (2020 Physical Review Letters, 2020)
Motivated by multiple possible physical realizations, we study the [SU](4) quantum antiferromagnet with a fundamental representation on each site of the triangular lattice. We provide evidence for a gapless liquid ground state of this system with an emergent Fermi surface of fractionalized fermionic partons coupled with a U(1) gauge field. Our conclusions are based on numerical simulations using the density matrix renormalization group method, which we support with a field theory analysis.